How much do CEOs really matter? Reaffirming that the CEO effect is mostly due to chance - Fitza, Markus A. (Strategic Management Journal, 2017)
How much of the variance in firm performance can be attributed to CEOs? This question has been the focus of a long debate in management research. In a recent study, I showed that a large portion of the performance differences that are often attributed to CEOs might in fact be due to chance. In a recent article, Quigley and Graffin argue that my conclusions can be avoided if more advanced methodological approaches are applied. Here I show that this is not the case, in fact if more realistic assumptions of how chance can affect firm performance are made, the effect of CEO leadership is almost indistinguishable from the effect of chance, independent of the estimation methodology. Copyright © 2016 John Wiley & Sons, Ltd.